Menulis Sebagai Media Ekspresi Diri Anak Sekolah Dasar - Astri Wulandari (Jurnal Sultra Elementary School, 2023)
Writing is one of the important language skills in education, especially for elementary school children. Writing activities not only function as a medium of communication, but also as a means of self-expression that allows children to express their thoughts, feelings, and imaginations. This article aims to examine the role of writing as a medium of self-expression for elementary school children through literature studies. The research method used is a literature review by analyzing various related studies. The results show that writing can increase creativity, critical thinking skills, and children's self-confidence. In addition, the use of appropriate learning approaches and interesting media has proven effective in motivating children to write.